Metodo e Questao Judaica em Hannah Arendt (Global Journal of Human-Social Science, 2021)
The article seeks to identify the methodological core of the Origins of Totalitarianism in the ideological origins of German misery. It then demonstrates how this perspective is mobilized in book 1 of the Origins of Totalitarianism, dedicated to the rise of modern anti-Semitism.
Keywords: arendt; metod; anti-semitism